Social Support dan Psychological Well Being terhadap Resiliensi Menghadapi Bencana - Albar, Ragwan; Fauziyah, Nailatin (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2022)
This study aims to find out the relationship between social support, psychological well-being, and resilience in disaster-resilient communities. Data collection techniques include the social support scale, the psychological well-being scale (PWBS), and the resilience scale. The study subjects numbered 81 people from Tangguh Bencana villagers who had received disaster mitigation. Data retrieval techniques use incidental sampling methods. The analysis method used is double regression. The results showed that simultaneously there is a relationship between social support and psychological well-being and resilience in the villagers of Tangguh disaster (p = 0.000). While the results of the study partially showed that there is a positive correlation between social support and resilience and a positive correlation between psychological well-being and resilience,. This means that the existence of good social and psychological well-being support contributes to the high resilience of tangguh disaster villagers in the face of difficult situations due to the disaster they face